Implementasi Pasal 30 Ayat 1 UUD 1945: Studi Kasus Peran Warga Dalam Meminimalisir Premanisme Di Kecamatan Jayamukti - Muhammad Rezki Hidayah; Muhamad Hasan Sebyar (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The phenomenon of criminality, especially street thuggery in Jayamukti Sub-district, Dumai City, Riau, is growing and cannot be denied. The existence of this thuggery gave birth to a group of criminals who committed violence. This thuggery violence can harm the surrounding community, especially in the social and economic fields. One of the factors in the birth of this thuggery is the increasingly difficult economic factors and the higher level of poverty. Thuggery in Jayamukti Sub-district, Dumai City, Riau is increasing due to many factors such as the economy, drugs, online gambling addiction, etc. The purpose of this research is to analyse the efforts of the local government to prevent thuggery. The purpose of this study is to analyse the efforts made by residents in minimising thuggery in Jayamukti sub-district, Dumai City, Riau. This research method uses the empirical juridical approach method, which means reviewing the state of the problem in the field associated with the legal aspects that apply and regulate the problem. The results of the research Thugs in the Jayamukti District area, Dumai City, Riau began to increase in the field of community life. Thugs commit extortion/pollution, brawl, stealing, etc. The role of citizens in minimising thuggery is reporting crimes committed by thugs to the authorities, as well as reducing social disorganisation, etc.